The phenomenon of pregnant Muslim marriages in Lintau Buo Utara, Tanah Datar, West Sumatra - Zulfan, Zulfan; Syarif, Makmur; Arlis, Arlis; Artalim Zaim, Muntaha; Taufiq, Arif (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, Indonesia, 2022)
A marriage where the woman is pregnant due to adultery is considered uncommon and taboo in Muslim society. The pregnancy is always kept secret by the prospective married couple and their families. The pregnant Muslim women marriage rate in Lintau Buo Utara is quite high. This study focuses on the case of pregnant women's marriages, specifically how the Office of Religious Affairs (KUA) officers may learn about the prospective bride's pregnancy and the family's actions after the prospective bride gives birth. The research was carried out in the form of a field study using the socio-legal research method with interviews conducted with relevant parties in this case. The results concluded that the majority of pregnant marriages at KUA Lintau Buo Utara were predominantly experienced by young couples at elementary and junior high education levels. KUA officials could discover about the future bride's pregnancy by observing the attitude of the prospective partner or their families during the registration process, the answers of the partner throughout the interview session, and the results of the examination done by the Public Health Center staff. The family's stance towards the pregnant woman's marriage is that the couple will hold a remarriage after the bride gives birth. The new findings in this study are related to the way KUA officers reveal the state of the prospective bride's pregnancy, which was originally kept secret. This is very important to be applicable to KUA officers in other areas.